Peningkatan Hasil Belajar Materi Qur’an Hadis Melalui Metode Student Teams Achievement Divisions (STAD) di Kelas 4 SDN 36 Air Amo - Permanen, Masdeni Semi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students' learning outcomes in the subject of Islamic Religious Education (PAI) focusing on the Qur'an Hadith element at SDN 36 Air Amo through the implementation of the Student Teams Achievement Divisions (STAD) method. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection phases. Data were collected through learning outcome evaluation tests, observations, and field notes. The results indicate that the STAD method significantly improves students' learning outcomes. In Cycle I, the average student scores were still low, with most students not meeting the minimum competency criteria (KKM). After improvements were made in Cycle II, there was a significant increase in average scores and the number of students meeting the KKM. Furthermore, this method enhanced students' active participation in the learning process.